Sunda pangolin (Manis javanica) responses to human impact in Sabah, Malaysia - JULIUS KODOH; CARMEN ADROS; NURASYIQIN AWANG SHAIRI; NORMAH AWANG BESAR; MOHD TAJUDDIN ABDULLAH; JEPHTE SOMPUD (Society for Indonesian Biodiversity, 2024)
Abstract. Kodoh J, Adros C, Shairi NA, Besar NA, Abdullah MT, Sompud J. 2024. Sunda pangolin responses to human impact in Sabah, Malaysia. Biodiversitas 25: 4233-4243. The Sunda pangolin (Manis javanica Desmarest, 1822), categorized as Critically Endangered, faces significant challenges due to human-driven threats, including poaching, habitat destruction, and illegal trade. The comprehensive impact of these factors remains underexplored, especially in specific locales such as the Universiti Malaysia Sabah (UMS) campus, Malaysia. This study, conducted from June to December 2023 within the Sustainable Forest Education Research Area (SFERA@UMS), evaluated the species' response to human disturbance through camera trap surveys. The investigation focused on how proximity to human settlements and noise pollution influence the distribution and behavior of M. javanica. Results from 1,647 camera-trap nights revealed that M. javanica demonstrated a preference for areas with reduced anthropogenic interference, shown by a weak yet significant positive correlation between greater distance from human settlements and pangolin presence (rs = 0.071**, p<0.001). Additionally, mean noise levels negatively impacted visitation frequency (rs = -0.075**, p<0.001), suggesting that noise pollution disrupts natural behaviors critical for survival, such as foraging. These results align with findings that wildlife, particularly species with secretive and nocturnal habits, tend to avoid regions with substantial human activity. The uneven spatial distribution of pangolins underscores the need for conservation initiatives that mitigate the adverse effects of human encroachment and noise pollution. Recommended actions include establishing buffer zones around critical habitats, enhancing public awareness, and employing technology for continuous monitoring. Integrating conservation strategies that address habitat quality, community involvement, and technological advancements is crucial for protecting M. javanica and supporting broader biodiversity efforts. These findings contribute to understanding the localized impacts of human activities on endangered species and highlight the importance of comprehensive, multi-faceted approaches for their conservation and habitat management.